Modern methods for radionuclide diagnosis of tumors and non-tumor pathologies of the brain - R. V. Zelchan; A. A. Medvedeva; O. D. Bragina; A. N. Ribina; A. I. Ryabova; V. I. Chernov; E. L. Choynzonov (Бюллетень сибирской медицины, 2022)
The review analyzes the global experience in the application of nuclear medicine techniques for diagnosis of tumors and non-tumor pathologies of the brain. The main groups of radiopharmaceuticals currently used for imaging of malignant brain tumors and diagnosis of cognitive impairments and neurotransmitter system disturbances by means of single-photon emission computed tomography and positron emission tomography are described.Modern approaches to the application of methods for radionuclide diagnosis in neuro-oncology and neurology are compared, and the main trends in production of new, more specific radiopharmaceuticals for visualizing brain tumors of various degrees of malignancy and diagnosing non-tumor pathologies of the brain are described. The review discusses the advantages and disadvantages of currently used techniques and radiopharmaceuticals for imaging of central nervous system disorders, depending on the clinical situation and specific diagnostic tasks.In addition, the review presents consolidated recommendations of the leading scientific schools in neuro-oncology on the use of nuclear medicine techniques in patients with brain tumors at the stages of treatment and follow-up. The presented article examines the experience of domestic scientific schools in the development of radiopharmaceuticals for neuro-oncology. The features of the development and use of new radiopharmaceuticals in patients with brain tumors and neurodegenerative diseases are highlighted. The review is based on the analysis of literature included in the Scopus, Web of Science, MedLine, The Cochrane Library, EMBASE, Global Health, and RSCI databases.